A short review of CdTe and CdSe films: growth and characterization - Ho, Soon Min; Vyas, C.U; Prarik, Pataniya; Patel, K.D; Somnath, Mahato (2018)
Cadmium based thin films including CdTe and CdSe show great potential for the use in the field of solar cells, optoelectronic and biomedical applications. This work gives a brief review of the preparation of CdSe, and CdTe films by using various deposition techniques. The chemical bath deposition method was used to deposit CdSe films using three precursors such as cadmium nitrate, cadmium sulfate and cadmium acetate are reported. Also, this article reviews on the experimental advances in electrodeposited of CdSe and screen printed cadmium telluride thin films. Various characterization techniques namely, X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDAX), scanning electron microscopy (SEM), UV-Visible spectrophotometer (UV-Vis) were used in the present research work have been discussed